2020
DOI: 10.3390/ijfs8020037
|View full text |Cite
|
Sign up to set email alerts
|

The Intersection of Islamic Microfinance and Women’s Empowerment: A Case Study of Baitul Maal Wat Tamwil in Indonesia

Abstract: It is largely assumed that Islamic microfinance institutions (IMFIs) deal with family empowerment instead of women’s empowerment. However, women are the main beneficiaries of Baitul Maal Wat Tamwil (BMT), Indonesia’s first IMFIs. This paper aims to explore the origins, the initiators, and the visions of BMTs and the extent to which they intersect with women’s empowerment. Employing a qualitative approach, this study selected four BMTs in Yogyakarta as a case study. It found that four critical groups that have … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 25 publications
(28 citation statements)
references
References 30 publications
0
14
0
1
Order By: Relevance
“…It offers asset-based financing such as Musharakah, Mudarabah and Salam. As highlighted by Rahayu (2020), Islamic microfinance has addressed some issues with exciting conventional microfinance including the non-conformity to Islamic values and principles. Indeed, using the structural equation model, Mansori et al (2020) conclude that religiosity has the highest impact on the individuals' intention to join Islamic microfinance products.…”
Section: Islamic Microfinance Featuresmentioning
confidence: 99%
See 1 more Smart Citation
“…It offers asset-based financing such as Musharakah, Mudarabah and Salam. As highlighted by Rahayu (2020), Islamic microfinance has addressed some issues with exciting conventional microfinance including the non-conformity to Islamic values and principles. Indeed, using the structural equation model, Mansori et al (2020) conclude that religiosity has the highest impact on the individuals' intention to join Islamic microfinance products.…”
Section: Islamic Microfinance Featuresmentioning
confidence: 99%
“…), so the extremely poor are not deprived of financing. Conventional microfinance is not usually appropriate for the chronically poor and destitute (Rahayu, 2020). Ghlamallah et al (2021) point out that the integration of zakat and waqf in the Islamic microfinance model is a specific "Islamic approach to philanthropic and inclusive finance.…”
Section: Islamic Microfinance Featuresmentioning
confidence: 99%
“…They suggested that MFIs extend their financial services to higher-income rural women to expedite women’s empowerment. Rahayu (2020) in a qualitative case study explored the relation between Islamic microfinance and women’s empowerment by Baitul Maal Wat Tamwil (BMT) in the Yogyakarta province of Indonesia. The study investigated only four selected BMTs and reported that none of them targeted women’s empowerment.…”
Section: Literature Reviewmentioning
confidence: 99%
“…With this model, it focuses on efforts to stretch the economy in the micro aspect. Second, Islamic finance through Islamic microfinance institutions as an instrument for empowering women (Rahayu, 2020;Nugroho and Chowdhury, 2015). The assumption is that providing affordable financial services for the poor is essential in increasing the poor's productivity and enhancing poor Muslims' economic development (Ahmed and Ammar, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…This study is based on the argument that native Papuan women "mama Papua" can compete if supported by credible financial instruments. The instrument referred to is empowerment assistance through donations and sustainable stakeholder support (Rahayu, 2020). As stated by Ahmed, E. M., and Ammar, capital through donations can positively contribute to micro and traditional businesses (Ahmed and Ammar, 2015).…”
Section: Introductionmentioning
confidence: 99%